2022
DOI: 10.1002/nop2.1506
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors influencing knowledge and self‐care practice among adults with type 2 diabetes mellitus

Abstract: The increasing prevalence of diabetes mellitus (DM) imposes a huge economic burden all over the world, particularly in sub-Saharan Africa where there are limited resources to manage the disease and its impact (Herrington et al., 2018;Islam et al., 2015). In 2017, it was estimated that 425 million people had diabetes worldwide with a corresponding global prevalence of 8.8% (International Diabetes Federation Report [IDF], 2017). The rates of DM have risen. An overwhelming 80% reside in low-and middle-income coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In general, it seems that insulin-treated participants have more T2D knowledge, particularly about the symptoms and complications, which may lead to a better self-care. According to Afaya et al (37), who found similar results, this can be due to a higher contact with health professionals, or these could pay a special attention to insulintreated patients in terms of education, to enable them to achieve better glycemic control, and so increasing their T2D knowledge. A specific access to healthcare for people with diabetes could improve knowledge, disease management, and health outcomes (49).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In general, it seems that insulin-treated participants have more T2D knowledge, particularly about the symptoms and complications, which may lead to a better self-care. According to Afaya et al (37), who found similar results, this can be due to a higher contact with health professionals, or these could pay a special attention to insulintreated patients in terms of education, to enable them to achieve better glycemic control, and so increasing their T2D knowledge. A specific access to healthcare for people with diabetes could improve knowledge, disease management, and health outcomes (49).…”
Section: Discussionmentioning
confidence: 83%
“…Diabetes is a complex management disease whose effectiveness depends, to a large extent, on the ability of people to cope with their knowledge, will, skills, and treating team for control and management of the clinical situation (37)(38)(39). Thus, the control of this health condition, as well as the prevention and delay of complications, are directly linked to decisions made by people with T2D, namely regarding diet, physical exercise, monitoring of glycemic control, and medication (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regular follow-up of diabetic patients by a multidisciplinary team is vital in averting long-term complications (9,10). This is met with difficulties as more than 80% of consultants in Kenya are found in Urban areas and tertiary hospitals, this in turn contributes to suboptimal diabetes management and higher rates of diabetesrelated complications (11).…”
Section: Introductionmentioning
confidence: 99%